CSPS: A small but stable society. (September 2021) - LaFosse, Mona Tokarek
The Canadian Society of Patristic Studies/Association Canadienne des Ètudes Patristiques (CSPS/ACÈP), founded in 1975, is dedicated to the study of early Christianity and its various contexts in Late Antiquity, drawing members from various disciplines from across Canada and internationally. The society welcomes and nurtures new scholars and seasoned members alike. Members are exposed to and discuss a broad range of patristic-related topics at the annual meeting because sessions normally run consecutively (not concurrently). Topics of particular interest in recent years include early Christian exegesis, material culture, Gnosticism (the Nag Hammadi texts, in particular), and Syrian patristics. It is a friendly, supportive, and rigorous academic environment in which to present one's work. The society strives to continue its bilingual roots as well as support new initiatives for the study of patristics in Canada.